Measuring the size distribution of microelectrodes in an array - Streeter, I; Compton, R (2008)
Microdisc arrays are considered for which the constituent disc electrodes are nonuniform in size. A method is described for using linear sweep voltammetry to calibrate the array to find the mean and standard deviation of the microdisc radii. Numerical simulation is used to model linear sweep voltammetry at arrays of single-sized microdiscs and of nonuniformly sized microdiscs. © 2007 Elsevier B.V. All rights reserved.